Traffic equilibrium methods - Florian, M. (Berlin : Springer, 1976)
This series aims to report new developments in mathematical economics, operations research, and mathematical systems, research and teaching - quickly, informally and at a high level
Procs-Int. Symp, Montreal Nov. 1974.
osc 04/07/2019
Loans
Keywords: Mathematical models